Silatuniq: Respectful state of being in the world - Annahatak, Betsy (Études/Inuit/Studies, 2014)
This paper focuses on silatuniq, a mode of being respectful or wise toward all that one encounters and interacts with in the world. Based on my personal background, I try to explain how Inuit in my region were culturally raised from childhood to adulthood to acquire values, skills, and knowledge to become competent in our society. This article is the result of my lifelong experience of having lived during a phase of cultural transition, from hunting camps to community life, then having lived as a student during the introduction of mainstream schooling in Kangirsuk, and finally working as an educator to make changes in Inuit education. A diagram illustrates how silatuniq, a sign of maturity, can be visualized as the central goal of the development of Inuit children as they acquire interrelated customary values and cultural rules. Hopefully this goal can apply to today’s Inuit schooling.